Safety Evaluation of Geometric Design Criteria: Horizontal Curve Radius and Side Friction Demand on Rural, Two-Lane Highways. Issue 3 (March 2019) - Himes, Scott; Porter, Richard J.; Hamilton, Ian; Donnell, Eric
AASHTO's A Policy on Geometric Design of Highways and Streets, 6 th Edition, provides design criteria for horizontal curve elements based on the point-mass model. The model equates the centripetal force needed to navigate a horizontal curve of a specific radius traveling at the design speed to the combination of superelevation rate and side friction needed to achieve that force. Few researchers have examined the safety impacts of horizontal curve radius, superelevation rate, and design speed through crash-based research. None of the research reviewed included the effects of design speed or superelevation rate in the crash modification factors (CMFs) or functions. This research explored these factors using a negative binomial regression modeling approach based on data collected from the SHRP 2 RID 2.0 for 889 horizontal curves on rural two-lane highways in Indiana and Pennsylvania, which resulted in roadway departure crash modification functions for horizontal curve radius and side friction demand. The crash modification function for side friction demand includes an interactive component of horizontal curve radius and speed and a direct effect of superelevation rate on roadway departure crashes. The results showed that roadway departure crashes are expected to increase for decreasing curve radius, increasing posted speed limit, and decreased superelevation rate. Furthermore, curve-related CMFs were sensitive to the curve radii used in their development. CMFs developed from curves with larger radii tended to result in larger CMFs. Sample applications are provided for computing the effects of changing the horizontal curve radius, posted speed limit, or both on proposed alternatives.